Dietary supplementation with hydroxypropyl-distarch phosphate from waxy maize starch increases resting energy expenditure by lowering the postprandial glucose-dependent insulinotropic polypeptide response in human subjects - Shimotoyodome, Akira; Suzuki, Junko; Kameo, Yoji; Hase, Tadashi (British journal of nutrition, 2011)
The aim of the present study was to investigate the effects of hydroxypropyl-distarch phosphate (HDP) supplementation on postprandial energy metabolism and glucose-dependent insulinotropic polypeptide (GIP) in human subjects. A total of ten healthy male subjects, with a mean BMI of 23·6 (sem 1·3) kg/m2, age 35·2 (sem 1·9) years and body weight 71·1 (sem 4·0) kg, participated in a randomised, cross-over, intervention study with two different test meals (1673·6 kJ) containing either waxy maize starch or HDP from waxy maize starch (degree of substitution 0·154, P content 0·004 %). Resting energy expenditure (REE) and blood concentrations of various biomarkers were measured at fasting and up to 180 min postprandially. Indirect calorimetry showed that the HDP meal caused higher REE (P < 0·05) and fat utilisation (P < 0·001) than the waxy maize starch meal. The HDP meal led to significantly lower postprandial glucose (P < 0·05), insulin (P < 0·05) and GIP (P < 0·05) responses than the waxy maize starch meal. Both postprandial REE (R − 0·576, P < 0·01) and fat utilisation (R − 0·514, P < 0·05) were negatively correlated with the postprandial GIP response, but not with the glucose and insulin responses. In conclusion, dietary supplementation with HDP lowers postprandial GIP and increases postprandial REE and fat utilisation in healthy humans. An HDP-rich diet may therefore have beneficial implications in weight management. Further studies are required to confirm the efficacy in overweight or obese subjects, and to determine the precise mechanisms.